Gastric emptying and the enzymatic activity in the stomach of Amphiprion ocellaris fed on artificial diet - Khoo, Mei Ling; Simon Kumar Das,; Mazlan Abd. Ghaffar., (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aims to elucidate the gastric emptying process of clownfish fed on artificial diet using two gastric evacuation models and to determine the pepsin activity in the digestion process in relation to feeding time. Regression analysis was used to evaluate the adequacy of 2 models; Anderson’s [St = So(1-So(α-1)ρ(1-α)t)1/(1-α) + ξ ] and Grove’s model [St = (Soα – αKt)1/α ], in describing the gastric emptying rate. Grove’s model provided a better fit with higher r2 value, with the calculated parameters of maximum meal size at time 0 (S0) = 0.195 g and gastric emptying rate (K) = 0.0165 g h-1. There was no initial delay phase as predicted and the evacuation followed a curve. Pepsin activity in the stomach showed rapid responses to food intake, where activity was detected at 1 h after feeding and reached its peak at 2 h after feeding. Pepsin activity decreased since then until the 12th h after feeding where it reached the lowest point. An increase of pepsin activity was detected later, where a small boost was detected at 24 h after feeding to digest the remaining food item in the stomach before the pepsin secretion decreased and maintained at pre-feeding level. Fast response of digestive enzyme in stomach implied that clownfish is equipped to utilize infrequent and irregular meals effectively.